Biotechnology and conservation of cultural heritage - Palla, Franco; Barresi, Giovanna (Springer, 2017)
This book provides detailed insights into the role of microorganisms and microbial products in biodeterioration, conservation and restoration of cultural heritage. Topics to be discussed are microbial colonization and their growth control on both artworks and aerosol of indoor environments such as libraries or museums, as well as human health hazard from exposure to microbial agents. In addition innovative biotechnological protocols and strategies for the removal of undesired layers on artwork surfaces are described in detail. Also the advances and perspectives in this emerging biotechnological field are discussed, supported by the latest original findings.- Resumé vydavatel
Keywords: kulturní dědictví; biodegradace; biotechnologie; konzervování archivních fondů; restaurování archivních fondů; památková péče; ochrana muzejních exponátů; cultural heritage; biodegradation; biotechnology; conservation of archival resources; restoration of archival resources; historic preservation; protection of museum exhibits; elektronické knihy; sborníky; electronic books; papers of several authors